Website-Based Contextual Learning Design of Han Script - Mulawarni Mulawarni; Emzir Emzir; Ratna Dewani (Teknodika, 2020)
This study aims to produce a website-based contextual learning prototype design of han script used for training of Han script learning by using a contextual approach. Prototype Research on Contextual Learning Design of Han Script Based on Website is the answer to the problems faced by Mandarin Language teachers in SMA/SMK/MA in learning Han script. By using the ADDIE model focused on the Design step based on document analysis and literature review, the 30 Han characters chosen for daily use based on the formation of the word 造字方法 "zào zì fāngfǎ. Seven stages in contextual learning implied in the website prototype named hanyupedia.id. The material is designed based on the data obtained from the needs analysis results consisting of material à Hànzì qǐyuán ，汉字 à hànzì jiégò，汉字造字法 hànzì zào zì fǎ and 汉字书法 à hànzì shūfǎ guīzé, which are available in the form of text, images, and videos for activity and training.